PROTECTING THE VULNERABLE IN SOUTH AFRICA: PROHIBITION OF CORPORAL PUNISHMENT IN THE PRIVATE SPHERE - Lizelle Ramaccio Calvino (Obiter, 2021)
On 18 September 2019, the Constitutional Court confirmed that the common-law defence of “reasonable and moderate chastisement” is unconstitutional as it unjustifiably violates sections 10 and 12(1)(c) of the Constitution of the Republic of South Africa, 1996. As a result, parents are no longer permitted to punish their child at home by way of inflicting physical punishment behind a facade of discipline. Despite the aforesaid, it should be noted that corporal punishment in the private sphere is not explicitly prohibited by South African legislation. In addition, South Africa’s legislative system lacks an appropriate regulatory framework to administer the anticipated proliferation of assault cases against parents. It is against this backdrop that this article first analyses the current legislative framework regulating the protection of children from physical punishment, and then follows with a succinct overview of the Constitutional Court ruling. The article assesses whether the mere repeal of the common-law defence of “reasonable and moderate” chastisement will be sufficient to eradicate corporal punishment in the private sphere, and if not, whether legislative prohibition and/or other interceding strategies will be required to give effect to the objective of the Constitutional Court ruling. In this regard, by way of comparative research, the legislative framework adopted by Sweden, being the first country in the world to prohibit all forms of corporate punishment of children is evaluated. Lastly, recommendations are made for the incorporation of practical steps, including possible legislative measures, to establish a regulatory framework from a children’s rights perspective to prohibit corporal punishment in the private sphere. Accordingly, for purposes of analysis and consideration, a qualitative approach is applied for purposes of the research. Primary sources such as the Constitution, case law, legislation, governmental documents, statistical data and research reports are consulted in conjunction with journal articles and textbooks.